Video as an anticipatory tool to deepen and to generate questions. A case study in higher education - Ferrari, Simona; Terrenghi, Ilaria (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2021)
Videos are today one of the most used tools in higher education, especially because of their practicality and efficacy: videos are easy to be filmed or to be found on the web and they can be used in many didactic or formative actions. Moreover, videos are able to enhance learning because they are more efficient than a static picture or frame. However, literature doesn’t show any evidence on the questions students develop after watching the video. Based on the previous considerations, we present a case study about a didactic event that has been redesigned, including some anticipatory videos as an innovative element. The overall aim of this study is to verify the video efficacy in terms of satisfaction and perceived impact on learning processes, interpreted through to the theoretical reference proposed by Schwartz and Hartman. The second aim is to understand how the anticipatory video helps students to deepen topics and to formulate specific and relevant questions. Data analysis shows that students perceive videos as useful tools to improve their engagement and motivation; to better understand some theoretical elements; and to focus on some details that would have been left out. The codification procedure shows that student’s questions are specific and coherent to the topic and that the students asked not only minimal explanations or clarifications but also some in-depth analysis of the experience. Considering that, we can say that videos could enhance preliminary and precise knowledge of the debated topic.